Ma‘had 'Aly and the Challenge of Modernizing Islamic Education in Indonesia - Firdaus Wajdi; Rihlah Nur Aulia (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
This paper discovers one of the pesantren models in Indonesia that is considered understudied, the University Level of Pesantren (Ma‘had ‘Aly), pesantren which santris are the university students. Particularly, this paper explains the struggle of Pondok Pesantren Darus Sunnah in facing the challenges of modernizing Islamic Education in Indonesia. Over time, the majority of pesantren adopted modernization to meet the demands from the society and to gain broader recognition from the government. However, the Pondok Pesantren Darus Sunnah is one of the pesantrens that delay the modernization. This paper aims at explaining the reasons for the reluctance of Pondok Pesantren Darus Sunnah to respond to the modernization. To answer the above question, this study employs a qualitative approach with auto-ethnography as the main data-collection tool. The author takes the advantage of the author's experience while being a santri and ustadz at the Darus Sunnah Islamic Boarding School with observations as additional data collection methods. In brief, this study suggests that the Pondok Pesantren Darus Sunnah currently rejects modernization because it reduces the authority and traditional identity of the pesantren. Pondok Pesantren Darus Sunnah prefers to keep the traditional pesantren in line with the advice of the charismatic founder of the pesantren. The traditional model of pesantren has been proven to have produced qualified alumni who play significant role both at national and international levels. This paper also proposes degree equivalence as a solution to this issue of modernizing Islamic education institution.